PENGARUH EARNING PER SHARE, PRICE TO BOOK VALUE, TINGKAT INFLASI, DAN NILAI KURS DOLLAR TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR INDUSTRI OTOMOTIF DAN KOMPONENNYA DI BURSA EFEK INDONESIA - Ayu Puspitaningtyas (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
Indicators like economic macro and firm financial performance had large influence toward stock price. The effect of those indicators could positive or negative. Many investigations show that economic macro and firm financial performance indicators such Earning Per Share, Price To Book Value, Inflation Rate and Exchange Rate have a positive or negative impact toward stock price. This research intended to further examine whether firm financial performance and economic macro indicators such Earning Per Share, Price To Book Value, inflation rate, and exchange rate influence to stock price in Automotive and Parts Industry during period 2006 – 2012, using multiple regression method. The samples were obtained with Purposive Sampling method from Automotive and Parts Industry . To this end, this research employed an empirical study by using 11 issuers. The hypothesis test result showed that the data had fulfilled classical assumptions such normally distributed, no multicollinearity and free from heteroscdasticity problem. The research showed that Earning Per Share and Price To Book Value has significant influence toward automotive and parts industry stock price. Mean while there is no significantly influence inflation rate and exchange rate when it was tested simultant or partially.